Corporate Risk Management and Hedge Accounting* - Panaretou, Argyro; Shackleton, Mark B.; Taylor, Paul A (Contemporary Accounting Research, 2013)
This paper provides evidence of the impact of hedge accounting under International Financial Reporting Standards (IFRS) on corporate risk man-agement. Using a sample of large UK non-financial firms from 2003 to 2006, we show that the implementation of the new standards reduces the level of asymmetric information faced by derivative users. Specifically, for firms that hedge under IFRS we find that analysts ’ forecast error and dispersion are significantly lower. The paper contributes to prior research on the effects of hedge accounting and on the adoption of IFRS.